1954
DOI: 10.2307/3894444
|View full text |Cite
|
Sign up to set email alerts
|

A Variation of Deferred Rotation Grazing for Use under Southwest Range Conditions

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…Transects were randomly established in parallel directions with a minimum of 50 m between transects. Pastoral units were each 40 ha and included a livestock exclosure unit, a high‐fenced livestock and deer exclosure unit, and two units that have been annually stocked with livestock under Merrill's four‐pasture deferred rotation system (Merrill ). Merrill's four‐pasture system rotates three herds of livestock among four pastoral units.…”
Section: Methodsmentioning
confidence: 99%
“…Transects were randomly established in parallel directions with a minimum of 50 m between transects. Pastoral units were each 40 ha and included a livestock exclosure unit, a high‐fenced livestock and deer exclosure unit, and two units that have been annually stocked with livestock under Merrill's four‐pasture deferred rotation system (Merrill ). Merrill's four‐pasture system rotates three herds of livestock among four pastoral units.…”
Section: Methodsmentioning
confidence: 99%
“…Herd movement in the Merrill rotation sequentially provided each pasture with a 4-month rest period following a 1-year grazing period (Merrill 1954).…”
Section: Grazing Treatmentmentioning
confidence: 99%
“…In a south Texas study, it was found that progressively increasing the stocking rate under short-duration grazing up 2.5 times the rate recommended by Merrill (1954) caused the frequency and composition of mid-grasses to decline but shortgrasses were not affected (Ralphs et al 1990). Standing crop of all major forage classes declined as stocking rate increased under short-duration grazing.…”
Section: Plant Succession and Range Conditionmentioning
confidence: 98%